Land-use Suitability is Not an Intrinsic Property of a Land Parcel - Ton Snelder; Linda Lilburne; Doug Booker; Amy Whitehead; Simon Harris; Scott Larned; Anette Semadeni-Davies; David Plew; Richard McDowell (Environmental Management, 2023)
Agricultural production has economic, environmental, social and cultural consequences beyond farm boundaries, but information about these impacts is not readily available to decision makers. This study applied the land use suitability concept by carrying out an assessment of a region that has the potential for intensification of agricultural production, but where eutrophication of river and estuary receiving environments due to nitrogen enrichment is a significant issue. The assessment evaluated three indicators for each farmable land parcel in the region: productive potential (the inherent productive and economic potential of the parcel), relative contribution (the potential for the parcel to contribute nitrogen to receiving environments compared to other land parcels), and pressure (the load of nitrogen delivered to receiving environments compared to the loads that ensure environmental objectives are achieved). The assessment indicated that land with high suitability for land-use intensification in Southland is limited because areas with high productive potential and low relative contribution rarely coincide with receiving environments with low pressure. Existing data, methods and models can be used to calculate the indicators under different choices for regional land-use intensity and receiving environment objectives. However, the spatial resolution and accuracy that is achievable may preclude using assessment outputs to make land use decisions at small spatial scales such as individual farms. The study highlighted that land use suitability is not an intrinsic property of a land parcel because it is dependent on choices about land use elsewhere in the landscape and the environmental objectives, and that land use suitability is inherently subjective because of decisions that concern how indicators are combined and weighted.